Mapping Fault Distribution Using Lineation and Fault Fracture Density Methods in the Palu Basin and Surrounding Areas - Livya. J. Pandesia; Abdullah; M. R. Muin (Tadulako Science and Technology Journal, 2023)
Introduction: Research has been carried out with the title "Mapping Fault Distribution Using Lineation and Fault Fracture Density Methods in the Palu Valley and Surrounding Areas" with the aim of determining the direction of fault distribution and analyzing fault density based on lineation data. Methods: This research uses the lineation method with a total of 40 grids. Data processing uses Global Mapper 18, rockwork 17, PCI Geomatica 2014, and Arcgis 10.8 software. Result and Discussion: The results obtained show that the lineation data from the dominant rose diagram has a relatively east-west direction. Areas that have high fault density are in Lindu District, Palolo District, Nokilalaki District, Gumbasa District, Dolo District, Sigi Biromaru District, and Mantikulore District with fault density values of 5,945 - 18,950/km2. Conclusion: The direction of lineation obtained tectonically is influenced by the Palu-Koro fault which tends relatively north-south, the Graben Palolo A and Graben Palolo B faults which trend relatively southeast-northwest, and the Lore Lindu fault zone. Areas with high density are weak zones that are vulnerable to natural disasters and potential https://www.surreyhillschallenge.com/ ground movements.